TANGGUNG JAWAB DEVELOPER BAGI KONSUMEN ATAS PERJANJIAN JUAL BELI RUMAH DENGAN MEKANISME PERJANJIAN PERIKATAN JUAL BELI (PPJB) - Christian Luther Manopo (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTBuying a house usually begins with PPJB as a binder between the developer and the consumer. However, over time, the implementation has been in many portraits of mourning that often reveal the news in the country that disappoints the public as consumers. The low awareness and knowledge of consumers so that they have a greater risk of consumer rights. The problem raised in this paper is the responsibility of the developer to the consumer for the house sale agreement with the mechanism of the sale and purchase agreement (PPJB) and the efforts that can be made by the consumer if the developer does not implement the sale and purchase agreement (PPJB).The type of research used is normative juridical with a statute approach.The responsibility of the developer to the consumer is the loss suffered by the consumer as regulated in Article 19 of Law Number 8 of 1999 concerning Consumer Protection. The developer is also responsible for correct information as well as building quality assurance. The developer's responsibility does not end there, during construction to the maintenance period the developer is also responsible for the quality of the building until the end of all sale and purchase binding agreements and the efforts made by consumers if the developer is unable to carry out the sale and purchase agreement (PPJB), namely, The first step is to ask the developer for existing problems, it can call or reprimand the developer. If it is not from the developer, it can file a lawsuit with the local district court. Keywords: Responsibility, Sale And Purchase Agreement, Developer